Evaluation of JC9450 and Neutral Electrolyzed Water in Controlling Listeria monocytogenes on Fresh Apples and Preventing Cross-Contamination - Sheng, Lina (Front Microbiol, 2020)
Recent multistate outbreaks and recalls of fresh apples due to Listeria monocytogenes contamination have increased consumer concerns regarding fresh and processed apple safety. This study aimed to evaluate the antimicrobial efficacy of two sanitizers, mineral oxychloride (JC9450) and neutral electrolyzed water (NEW), for inactivation of L. monocytogenes on fresh apples. A 2-min treatment of 0.125% (v/v) JC9450 with 100 ppm free available chlorine (FAC) or NEW with 110 ppm FAC caused 0.9–1.2 log(10) CFU/apple reduction of L. monocytogenes on both Granny Smith and Fuji apples 24 h post-inoculation. Increasing JC9450 concentration to 0.25 and 0.50% significantly improved its bactericidal effect and reduced L. monocytogenes on Granny Smith apples by ~2.0 and 3.8 log(10) CFU/apple, respectively, after a contact time of 2 min. At a shorter contact time of 30 sec, the inactivation efficacy of chlorine and 0.25–0.50% JC9450 against L. monocytogenes on apples was significantly reduced compared with the respective 2-min wash. Furthermore, no L. monocytogenes was recovered in deionized water prepared antimicrobial wash solution or on non-inoculated apples post-NEW with 110 ppm FAC or 0.125–0.5% JC9450 washes, indicating their ability to prevent cross-contamination. In addition, a 2-min exposure to NEW with 110 ppm FAC and 0.50% JC9450 reduced apple native microbiota including total plate count by 0.14 and 0.65 log(10) CFU/apple, respectively, and yeast and mold counts by 0.55 and 1.63 log(10) CFU/apple, respectively. In summary, L. monocytogenes attached on apples was difficult to eliminate. JC9450 and NEW demonstrated a dose-dependent reduction in L. monocytogenes on apples and successfully prevented cross-contamination, indicating their application potential in post-harvest washes of apples.